2014
DOI: 10.15376/biores.9.4.7222-7233
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity and Characterization of Wood Fibers Modified by Alkoxysilanes with Different Chain Lengths

Abstract: As the main raw material for fiberboard, the hygroscopicity of wood fibers is of great concern. In this study, three alkoxysilanes with different chain lengths-methyl trimethoxy silane (MTMS), octyl trimethoxy silane (OTMS), and dodecyl trimethoxysilane (DTMS)-were used respectively to treat wood fibers to reduce their hygroscopicity and surface hydrophilicity. After alkoyxilane properties were evaluated, the chemical structures, surface groups, and morphology and distribution of alkoxysilanes within modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…These results are comparable to previous results from Ouyang et al, who reported a C-C and C-H concentration of 90.26% for a dodecyltrimethoxysilane (DTMS)functionalized wood ber surface. 38 For BTES-functionalized surfaces, the aromatic ring leads to characteristic p-p* satellite structures, as reected near 291.2 eV in Fig. 3b, 44,45 As shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These results are comparable to previous results from Ouyang et al, who reported a C-C and C-H concentration of 90.26% for a dodecyltrimethoxysilane (DTMS)functionalized wood ber surface. 38 For BTES-functionalized surfaces, the aromatic ring leads to characteristic p-p* satellite structures, as reected near 291.2 eV in Fig. 3b, 44,45 As shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…36,37 The strong peaks between 2800 and 3000 cm À1 in DTESfunctionalized surfaces are characteristic of C-H stretching from the long alkyl chains. 38 The absorption peak (Fig. 1b) for MAPTES at approximately 2900 cm À1 is attributed to C-H stretching, and the band around 1720 cm À1 is associated with C]O stretching.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that silanes treatment could limit even more the hygroscopicity of wood, compared to thermal treatment under specific conditions, probably because silane molecules are capable of filling the large pores of wood cell cavities and reacting with the hydroxyl groups. Therefore, the long chains of the silane manage to hinder the degree of moisture uptake [36], improving the dimensional stability and surface hydrophobicity of silane-modified wood. Additionally, by increasing the participation of benzin in the organosilane solutions against the participation of water as a solvent, the EMC seems to be even lower, which could be possibly attributed to better performance and the slightly higher absorption of the silane solution in the mass of wood during the surface modification.…”
Section: Thermally-chemically-treated Black Pinementioning
confidence: 99%
“…Thus, AAS pre-impregnation limited the degradation of cell wall components during the thermal treatment. In addition, the AAStreated samples showed new absorption bands at 1257 cm -1 , 1080 cm -1 , 798 cm -1 , and 450 cm -1 , which corresponded to ν (Si-C) stretch vibration, skeletal vibration δ (Si-O-Si), ν (Si-C) and/or ν (Si-O), and weak vibration δ (O-Si-O), respectively (Sèbe et al 2004;Tinguat et al 2005;Ghosh et al 2009;Ouyang et al 2014). These peak changes demonstrated that AAS reacted with the hydroxyl groups in the wood cell wall.…”
Section: Chemical Analysismentioning
confidence: 99%